2012
DOI: 10.1002/ajim.22119
|View full text |Cite
|
Sign up to set email alerts
|

The effect of occupational exposure to benzo[a]pyrene on neurobehavioral function in coke oven workers

Abstract: Occupational exposure to B[a]P is associated with neurobehavioral function impairment in coke oven workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 48 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Findings of another study monitored digital span and order digital span scores showed that memory and learning abilities were considerably reduced in coke oven workers [21]. Also the performances on correct pursuit aiming, simple reaction time, and error pursuit aiming have been shown to decrease in coke oven workers exposed to airborne enzo [α] pyree [22]. It seems that not only many other factors involved in workers' lifestyles which are engaged in neurocognitive impairment, but also unknown roles of the oxidative stress with a highlighted background in damaging different parts of nervous system should not be ignored, particularly in long term exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of another study monitored digital span and order digital span scores showed that memory and learning abilities were considerably reduced in coke oven workers [21]. Also the performances on correct pursuit aiming, simple reaction time, and error pursuit aiming have been shown to decrease in coke oven workers exposed to airborne enzo [α] pyree [22]. It seems that not only many other factors involved in workers' lifestyles which are engaged in neurocognitive impairment, but also unknown roles of the oxidative stress with a highlighted background in damaging different parts of nervous system should not be ignored, particularly in long term exposures.…”
Section: Discussionmentioning
confidence: 99%
“…As compared to PAH mixtures, B[a]P confers a higher health risk in terms of immunosuppression, carcinogenicity, teratogenicity, and mutagenicity. It is well-known that B [a]P plays a critical role in the initiation of cancers in lung at its first proximity, and inducing cell proliferation is one of the early occurrence prior to cell malignant transformation (Qiu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, coke-oven workers in China had lower learning-ability and memorization-test performance that correlated with levels of the PAH 1-OH-pyrene in urine [12]. Mechanistically, exposure to B[a]P was linked to memory and learning disabilities in these coke-oven workers by a reduction in choline, monoamine and amino acid neurotransmitter levels [12,13]. Occupational exposure is not the only concern, however.…”
Section: Introductionmentioning
confidence: 99%